Pengaruh Manajemen Sumber Daya Manusia Terhadap Prestasi Belajar Peserta Didik di SMPN 1 Cikampek - Afrilia, Arneta; Permana, Hinggil; Husein, Ceceng Syarif (Jurnal Ilmiah Wahana Pendidikan, 2024)
The research aims to determine the effect of human resource management on student learning achievement at SMPN 1 Cikampel. This type of research uses quantitative methos through a correlational approach. The population in this study was 100 tool respondents the measure used is an instrument for collecting quantitative data or statistics. The data analysis technique used is statistical data analysis descriptive and inferential statistical analysis. Based on data analysis techniques, human resource management on student learning achievement is included in teh medium category.